Frontispiece: Nanoporous Films with Oriented Arrays of Molecular Motors for Photoswitching the Guest Adsorption and Diffusion. Issue 3 (9th January 2023) - Jiang, Yunzhe; Danowski, Wojciech; Feringa, Ben L.; Heinke, Lars
Abstract : Photochromic Materials . In their Communication (e202214202 ), Lars Heinke et al. report nanoporous films with oriented arrays of molecular motors for light‐controlled adsorption and diffusion.